Dual-band lasing from ZnO/CsPbBr3 core/shell microcavity. (25th September 2019) - Zhang, Wei; Xu, Chunxiang; You, Daotong; Wang, Ru; Chen, Feng; Liu, Wei; Shi, Zengliang; Cui, Qiannan
Abstract: It is a challenge to design and fabricate micro/nano-scaled dual-band even multi-band lasers for potential nanophotonic application. Here, a ZnO/CsPbBr3 core/shell microrod was fabricated as a hybrid microcavity for dual-band lasing. The stimulated ultraviolet and visible emission was realized simultaneously under the optical pumping. The lasing properties and the resonance mechanism of the dual-band laser was investigated experimentally and confirmed by 2D finite difference time domain simulation.